Design and implementation of a teaching-learning sequence of the chemical element concept in high school education - López, Dulce María (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article proposes the implementation of a teaching-learning sequence based on the model of learning in the context of an oriented research, in order to improve the teaching of the chemical element concept in high school education. Its design is based on the students’ existing ideas and on the historical analysis about this concept. The evaluation was made by comparing groups of students who followed this didactic sequence to groups of students who maintained a traditional teaching. The results show that the students in the experimental groups compared to the control groups: 1) they present a better understanding of the procedural definition of substance at the macroscopic level; 2) they better define the concept of chemical element within the framework of the Daltonian theory; 3) they better distinguish the concepts of simple substance and chemical element; and 4) they demonstrate a better differentiation of the microscopic concept of mixture—of simple substances or of compounds—when a didactic sequence of constructivist orientation is used.